Global water stress mitigation achieved through international crop trade - Ying Shi; Xu Zhao; Martin R. Tillotson; Xinxin Zhang; Rui Zhong; Honglin Zhong (iScience, 2025)
Summary: Global water savings can be achieved by trading crops from countries with higher to lower water productivity. However, strengthening such water-saving trade links could intensify global water stress if exports come from water-stressed countries to less stressed ones. Here, we explore whether international crop trade can alleviate global water stress using a virtual scarce water saving/loss indicator and refined trade matrices for 109 crops across 150 countries. We further assess how differences in water productivity and stress between trade partners mitigate global water stress by categorizing different types of crop trade relationships. Our results indicate that while international crop trade generally helps mitigate global water stress, over half of the trade links still contribute to increased water stress. Scenario analysis suggests that enhancing crop water productivity among exporters involved in virtual scarce water loss trade links could convert up to 53% of these loss links into saving links.